Orthodontic treatment considerations in Down syndrome patients - Sianiwati Goenharto (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Down syndrome is an easily recognized congenital disease anomaly, a common autosomal chromosomal anomaly with high prevalence of malocclusion. Orthodontic treatment demand should be high but it seems difficult to be done because of specific condition of disability. Purpose: The purpose of this literature review was to discribe the orthodontic problems found in Down syndrome patients and several consideration that shoud be done to treat them. Reviews: Many studies report the high prevalence of malocclusion among people with Down syndrome. There is a greater frequency of clas III relationship, crossbite, crowding and also open bite. Several problems might appear in the treatment because of dental, medical, mental, and behavioural factor. Conclusion: It is concluded that orthodonic treatment can be performed in Down syndrome patient, although several difficulties may appear. Good consideration in mental, behavior, medical and also dental condition will influence whether the treatment will success or not. Special care and facilities will support the orthodontic treatment.Latar belakang: Sindroma Down adalah suatu kelainan congenital yang mudah dikenali, merupakan kelaian kromosom autosomal yang cukup banyak terjadi, dengan prevalensi maloklusi cukup tinggi. Seharusnya permintaan akan perawatan ortodonti juga tinggi meskipun tampaknya sulit dilakukan karena adanya kondisi ketidakmampuan/cacat yang spesifik. Tujuan: Tujuan studi pustaka ini adalah untuk menggambarkan problem perawatan ortodonti pada penderita sindroma Down dan pertimbangan apa yang sebaiknya diambil untuk mengatasi masalah tersebut. Tinjauan pustaka: Banyak penelitian melaporkan tentang prevalensi maloklusi yang tinggi pada penderita sindroma Down. Maloklusi yang sering dijumpai adalah relasi klas III, gigitan silang, berdesakan dan juga gigitan terbuka. Problem dapat terjadi saat perawatan ortodonti karena adanya faktor dental, medis, mental dan tingkah laku penderita. Kesimpulan: Disimpulkan bahwa perawatan ortodonti masih dapat dilakukan pada penderita sindroma Down meskipun dengan beberapa kesulitan. Pertimbangan mental, tingkah laku, kondisi medis sistemik dan kondisi dental, akan mempengaruhi hasil perawatan. Tindakan dan fasilitas khusus diperlukan untuk menunjang suksesnya perawatan ortodonti pada penderita sindroma Down.